Diagnostic and prognostic value of the electrocardiogram in stable outpatients with type 2 diabetes. (31st December 2022) - Gregers, Mads C. T.; Schou, Morten; Jensen, Magnus T.; Jensen, Jesper; Petrie, Mark C.; Vilsbøll, Tina; Goetze, Jens Peter; Rossing, Peter; Jørgensen, Peter G.
Abstract: Aims . The European Society of Cardiology guidelines on diabetes and cardiovascular disease (CVD) recommend an electrocardiogram (ECG) in patients with diabetes and hypertension or with suspected CVD. We investigated whether ECG abnormalities can be used as a diagnostic and prognostic marker of heart failure (HF) in patients with type-2 diabetes (T2D) in secondary care diabetes-clinics. Methods . We included 722 patients with T2D in sinus rhythm. HF with preserved ejection fraction (HFpEF) was defined according to the European Society of Cardiology guidelines. Heart failure with mid-range ejection fraction (HFmrEF) was patients with dyspnoea and an LVEF 41–49%. Heart failure with reduced ejection fraction (HFrEF) or asymptomatic left ventricular systolic dysfunction (ALVSD) was defined as a LVEF ≤40%. Results . Overall, 24% patients had ECG abnormalities. A total of 15% had HF whereof 48% had ECG abnormalities. A normal ECG had a 99.3% negative predictive value (NPV) of ruling out HFrEF/ALVSD. In a sub-group with 0-1 simple clinical risk markers, the ECG ruled out both HFrEF/ALVSD, HFmrEF, and HFpEF with an NPV of 96.6%. The hazard-ratio (HR) of incident CVD or death in patients with HF and a normal ECG compared with patients without HF was 1.85 [95%CI 1.01–3.39], p = .05, while an abnormal ECG increased the HR to 3.84 [2.33–6.33], p < .001. Conclusion . HFrEF/ALVSD and HFmrEF were rare and HFpEF was frequent in this T2D population. A normal ECG ruled out HFrEF/ALVSD and in a sub-population with 0–1 simple clinical risk markers also both HFrEF/ALVSD, HFmrEF, and HFpEF. Key messages: What is already known about this subject? In early studies of unselected patients from primary care with suspected chronic heart failure, the presence of a normal ECG was found be useful to rule out heart failure with reduced ejection fraction. What does this study add? This study confirms that a standard electrocardiogram when normal in 722 stable outpatients with type 2 diabetes can be used to rule out HFrEF/ALVSD. Further, it adds knowledge about the risk of incident cardiovascular disease or death as a pathologic electrocardiogram increases the hazard ratio. How might this implicate clinical practice? With this study clinicians in secondary diabetes care clinics can use an electrocardiogram to select patients to undergo echocardiography when suspecting heart failure with reduced ejection fraction, as a normal electrocardiogram will rule out this diagnosis with a negative predictive value of >99%.